Diffusion tensor tractography: Two methods comparative evaluation for gliomas presurgical workup - Hassanein, Sara (Neuro Oncol, 2018)
BACKGROUND: Glioma is the most common primary brain tumour, characterized by invasive growth along white matter (WM) fiber tracts. Tractography providesan importantanatomic guidance in the preoperative planning process, which aims at maximizing resection whilst minimising morbidity. This study aimed atdetermining the agreement between two different software packages for delineating corticospinal tract (CST), arcuate fasciculus (AF) and optic radiation (OR). METHODS: Forty-six histopathologically proven gliomapatients subdivided into:groupA with tracts passing at the tumour margin; and groupB with tracts passing through tumour and/or in the peritumoural oedema. FSL and MRTrix software were used for tracking, in each patient,CST (hand, foot and lips component), AF and OR using the same regions of interest. Qualitative evaluation of the agreement between the two methods was performed by two experienced observers in consensus. RESULTS: The tracts identified: Were comparable for: CST-foot in 8(5) out of 11(8) cases in groupA (B); CST-hand in 6 out of 8 cases in groupB; Had less false positives in MRTrix for: CST-hand in 7 out of 11 cases in groupA; CST-lips in 5(6) out of 8(8) cases in groupA (B); AF in 4(8) out of 7(9) cases in groupA (B); Were more accurate in FSL for: OR in 6(6) out of 6(7) cases in groupA (B). CONCLUSIONS: The accuracy of the tracts is comparable for most fascicle identification, with the exception of MRTrix presenting less false positives for AF in groupB, CST-hand in groupA and CST-lips in groupsA and B; and FSL identifying more accurately the OR in both groups.